“Enhancing the Sustainability Banking In Indian Banking Sector: A Pathway to Responsible Finance” - Sharma , Aishwarya (Trinity Law Review, 2024)
Sustainable banking, also known as ethical banking or  green banking, is a concept where banks focus on making  money and consider the environmental and social impacts  of their financial activities. It involves making responsible  and ethical economic decisions that support the planet’s  and society’s well-being. Sustainable banks aim to balance  profit-making with environmental conservation, social  equity, and ethical practices. They often invest in environ mentally friendly projects, support social initiatives, and  adopt eco-friendly banking practices to promote a more  sustainable and responsible financial system.
Keywords: degradation; financial system; broader